Relation of Serum Level of Lipocalin 2 to Her2/neu in Women with Breast Cancer - Atheer R. Atia1 , Salam S. Ahmed2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Breast cancer is the most common type of cancer worldwide, being one of the leading causes morbidity in the female.(1) Lipocalin is a neutrophil gelatinase-associated lipocalin (NGAL) or lipocalin 2 that is a 25 KDa glycoprotein, which was originally identified as a covalent complex with matrix metalloproteinase-9 (MMP-9) in human neutrophil.(2) Lipocalin acts as bone-derived hormone which crosses the blood brain barrier (BBB) and acts on the hypothalamus in the brain. The human epidermal growth factor receptor 2 (HER-2/neu), has shown to have a prognostic value for the treatment with the monoclonal antibody in breast cancer.(3) Material and Method: This is a cross sectional, hospital based study. This study was carried out at the Oncology Center in Kirkuk City-Iraq from the 1st of November 2018 to the end of June 2019. Forty-two women with breast cancer were considered as a study group. Forty-four apparently healthy women without breast cancer (relative of patients) and with a negative family history for the first and second degree relatives of breast cancer were consider as a control group, their ages were from 23 to 70 year. By using a sterile disposable syringe 10 mls of venous blood sample was drawn from each woman at morning and was kept in a plain tube and allowed to clot at room temperature, then each sample was centrifuged at 6000 rpm to obtain serum. Serum of the patients and controls had assay for lipocalin 2 and Her2/neu by ELISA. Results: The mean serum level of lipocalin 2 was significantly elevated in breast cancer women compared to control women (62.77 ± 6.1 and 23.98 ± 5.9 ng/l) respectively at a P value of 0.001. This study also reveals that the mean serum level of Her2/neu was higher in breast cancer women (33.96 ± 2.7 ng/ml) as compared with the control group (9.76 ± 1.6 ng/ml). This result was highly significant at a P value of 0.001. This study found that there was a moderate positive correlation between lipocalin with Her2/neu in breast cancer women (R: 0.33), which means that lipocalin 2 was proportionally elevated with increasing of Her2/ neu level. Conclusion: This study reveals that there was a significant positive correlation between lipocalin and Her2/ neu in breast cancer women, the r value was 0.33.